2014
DOI: 10.1016/j.celrep.2014.10.059
|View full text |Cite
|
Sign up to set email alerts
|

Cohesin Rad21 Mediates Loss of Heterozygosity and Is Upregulated via Wnt Promoting Transcriptional Dysregulation in Gastrointestinal Tumors

Abstract: Loss of heterozygosity (LOH) of the adenomatous polyposis coli (APC) gene triggers a series of molecular events leading to intestinal adenomagenesis. Haploinsufficiency of the cohesin Rad21 influences multiple initiating events in colorectal cancer (CRC). We identify Rad21 as a gatekeeper of LOH and a β-catenin target gene and provide evidence that Wnt pathway activation drives RAD21 expression in human CRC. Genome-wide analyses identified Rad21 as a key transcriptional regulator of critical CRC genes and long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 46 publications
4
35
0
Order By: Relevance
“…Indeed activated Cyclin E1 through its promotion of CIN accelerates LOH (47) with Apc wt LOH having been shown to be a key event in adenoma formation in the Apc Min/þ mouse (48). Indeed, we have recently shown that CIN begins immediately following the loss of the WT allele in Apc Min/þ organoid cultures (49). Furthermore, we observed a decrease in chromosomal abnormalities in CT26 cells, most notably the degree of tetraploidy with Cyclin E1 knockdown.…”
Section: Discussionsupporting
confidence: 51%
“…Indeed activated Cyclin E1 through its promotion of CIN accelerates LOH (47) with Apc wt LOH having been shown to be a key event in adenoma formation in the Apc Min/þ mouse (48). Indeed, we have recently shown that CIN begins immediately following the loss of the WT allele in Apc Min/þ organoid cultures (49). Furthermore, we observed a decrease in chromosomal abnormalities in CT26 cells, most notably the degree of tetraploidy with Cyclin E1 knockdown.…”
Section: Discussionsupporting
confidence: 51%
“…21 In prognostic analyses, SCC1/RAD21 overexpression has been associated with poor prognosis in high-grade luminal, basal, and Her2-amplified breast cancer subgroups. 22 Corresponding results on SCC1/RAD21 overexpression and an unfavorable prognosis have been achieved from human prostate cancer, 23 myeloid malignancies, 24 and colorectal cancer. 22 SMC1 subunit overexpression has been detected in a panel of triple-negative breast cancer cell lines, but not in hormone-receptor-positive breast cancer cells.…”
Section: Discussionmentioning
confidence: 86%
“…Rad21 is a member of the cohesin family, which is activated by the Wnt/β-catenin pathway. In human CRC cell lines, 87 L1 was found to be activated by Rad21, leading to speculation that L1 activation might be linked to the oncogenic Wnt/β-catenin pathway. Associations between p53 deficiency and L1 expression or hypomethylation were observed in multiple cancers.…”
Section: Perspectives: Implications Of L1 Activity and Expression In mentioning
confidence: 99%